Islamic and modern science perspectives issues of animal plasma as a source of food additives in food products - Ahmad Fadzillah, Nurrulhidayah; Mohd Sukri, Siti Jamilah; Mat Jubri@Shamsuddin, Mustafa; Abd. Mutalib, Sahilah; Rosman, Arieff Salleh; Rohman, Abdul; Ramli, Mohd Anuar; Kurt, Nurullah (International Association of Engineering and Management Education (IAEME), 2020)
Disposal of animal blood from slaughterhouses leads to high risk of water and land resources problem. Due of this concern, food scientists separated the plasma component and transformed into food additives that comprised with tremendous functional properties such as gelling agent, replacing fat and eggs function, emulsifier, binder agent and also has been used as an alternative supplement to boost up human’s immune system. This phenomenon is also witnessing emergence of leading key players who globalized animal plasma derivatives market around worldwide food industry. This has raised the concern among the Muslim consumers because consuming any blood and its derivatives are strictly prohibited in Islam mainly spilled out blood. Due to this restriction, modern science techniques are also crucial to detect the presence of animal plasma into food products as it is impossible to be detected through human’s naked eyes. Therefore, this paper is purposely written down to highlight Islamic and modern scientific perspectives on the issues of animal plasma as a source of food additives in food products. It is hoped this paper will be a good reference and motivates other researchers to do more research in the context of variety scope in future.